Cross‐protective efficacy of a live‐attenuated Edwardsiella ictaluri vaccine against heterologous Edwardsiella piscicida isolates in channel and channel × blue catfish hybrids. Issue 7 (25th April 2022) - López‐Porras, Adrián; Griffin, Matt J.; Ware, Cynthia; Richardson, Bradley M.; Greenway, Terrence E.; Graham Rosser, Thomas; Aarattuthodiyi, Suja; Wise, David J.
Abstract: Edwardsiella piscicida is a growing problem for catfish aquaculture in the southeastern United States, particularly in channel ( Ictalurus punctatus ) x blue ( I. furcatus ) catfish hybrids. Research has shown E. piscicida isolates recovered from farmed catfish in Mississippi form at least five discrete phyletic groups, with no apparent differences in virulence in channel and hybrid catfish. Laboratory trials have shown a live‐attenuated E . ictaluri vaccine (340X2) cross‐protects against at least one E. piscicida isolate (S11–285) in channel and hybrid catfish, although it is unknown if this protection exists for other E. piscicida variants. To this end, channel and hybrid catfish were immunized by immersion with E . ictaluri 340X2. Thirty days later, fish were challenged by intracoelomic injection with representative E. piscicida variants from each phyletic group. Relative percent survival (RPS) for hybrids ranged from 54.7% to 77.8%, while RPS in channels ranged from 80.5% to 100%. A second study investigated whether channel and hybrid catfish exposed to heterologous E. piscicida isolates were similarly protected against wild‐type E . ictaluri . Fish were exposed by bath immersion to representative E. piscicida isolates from each phyletic group. Thirty days post‐immunization, fish were challenged by immersion with wild‐type E . ictaluri isolate S97–773. Regardless of variant, previous exposure to heterologous E. piscicida isolates significantly improved survival following E . ictaluri challenge. These findings suggest the presence of shared and conserved antigens among E. piscicida and E . ictaluri that could be exploited by application of polyvalent or cross‐protective vaccines.